2015
DOI: 10.1017/jfm.2015.196
|View full text |Cite
|
Sign up to set email alerts
|

A numerical evaluation of the asymptotic theory of receptivity for subsonic compressible boundary layers

Abstract: The capabilities of the triple-deck theory of receptivity for subsonic compressible boundary layers have been thoroughly investigated through comparisons with numerical simulations of the compressible Navier-Stokes equations. The analysis focused on the two Tollmien-Schlichting wave linear receptivity problems arising due to the interaction between a low amplitude acoustic wave and a small isolated roughness element and the low amplitude, time-periodic vibrations of a ribbon placed on the wall of a flat plate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…At the same time, we know from a number of comparisons of the triple-deck theory with the Navier-Stokes simulations of the boundary-layer receptivity in subsonic flows that the triple-deck predictions are rather accurate (see e.g. Tumin 2006;Tullio & Ruban 2015). Therefore, we expect the results presented in this paper to be sufficiently accurate for engineering applications.…”
Section: Discussion Of the Resultsmentioning
confidence: 67%
“…At the same time, we know from a number of comparisons of the triple-deck theory with the Navier-Stokes simulations of the boundary-layer receptivity in subsonic flows that the triple-deck predictions are rather accurate (see e.g. Tumin 2006;Tullio & Ruban 2015). Therefore, we expect the results presented in this paper to be sufficiently accurate for engineering applications.…”
Section: Discussion Of the Resultsmentioning
confidence: 67%
“…The parabolized stability equations 22,32,33 also partially capture non-parallel flow effects. 41 took on the acoustic receptivity problem by solving the compressible unsteady Navier-Stokes equations to compute the steady basic flows, and the LNS equations to obtain the unsteady perturbations. The vast majority of these works are computationally demanding, thus severely limiting their applicability in sensitivity and parametric investigations or design optimization analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for pursuing this methodology are threefold: it is general and versatile enough to accommodate different receptivity mechanisms (vorticity, wing vibration, suction, heating) 17 , a wide range of flow conditions 41 , and finally non-linear corrections (both due to finite-height roughness and interaction of acoustic modes). It is sufficiently fast to be used recurrently (one acoustic frequency scenario can currently be computed in under 5 minutes approximately, using 20 CPU cores), while also enjoying the advantage of being able to calculate receptivity amplitudes for a range of different roughness shapes at little additional computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…For example, comparisons with experiments (Wu 2001a, b) indicate that the theory, especially with the extension to second-order accuracy, predicts fairly accurately receptivity in the incompressible regime. Recent DNS studies (Mengaldo et al 2015, De Tullio & Ruban 2015 showed that the same is true for subsonic boundary layers. Nevertheless, further work is still needed in order to validate the present theoretical results for supersonic boundary layers.…”
Section: Discussionmentioning
confidence: 81%